In Vitro and In Vivo Antifungal Profile of a Novel and Long-Acting Inhaled Azole, PC945, on Aspergillus fumigatus Infection - Colley, Thomas; Alanio, Alexandre; Kelly, Steven L; Sehra, Gurpreet; Kizawa, Yasuo; Warrilow, Andrew G S; Parker, Josie E; Kelly, Diane E; Kimura, Genki; Anderson-Dring, Lauren; Nakaoki, Takahiro; Sunose, Mihiro; et al. (Antimicrobial agents and chemotherapy, 2017)
The profile of PC945, a novel triazole antifungal designed for administration via inhalation, was assessed in a range of and studies. PC945 was characterized as a potent, tightly binding inhibitor of sterol 14α-demethylase (CYP51A and CYP51B) activity (50% inhibitory concentrations [IC s], 0.23 μM and 0.22 μM, respectively) with characteristic type II azole binding spectra. Against 96 clinically isolated strains, the MIC values of PC945 ranged from 0.032 to >8 μg/ml, while those of voriconazole ranged from 0.064 to 4 μg/ml. Spectrophotometric analysis of the effects of PC945 against itraconazole-susceptible and -resistant growth yielded IC (determined based on optical density [OD]) values of 0.0012 to 0.034 μg/ml, whereas voriconazole (0.019 to >1 μg/ml) was less effective than PC945. PC945 was effective against a broad spectrum of pathogenic fungi (with MICs ranging from 0.0078 to 2 μg/ml), including , , , , , , , and (1 or 2 isolates each). In addition, when hyphae or human bronchial cells were treated with PC945 and then washed, PC945 was found to be absorbed quickly into both target and nontarget cells and to produce persistent antifungal effects. Among temporarily neutropenic immunocompromised mice infected with intranasally, 50% of the animals survived until day 7 when treated intranasally with PC945 at 0.56 μg/mouse, while posaconazole showed similar effects (44%) at 14 μg/mouse. This profile affirms that topical treatment with PC945 should provide potent antifungal activity in the lung.